How do our students learn clinical engineering? A pilot study (2017)
This paper aims to measure what are the students’ perceived learning outcome achievements after finishing their clinical engineering major courses. This is a pre- post-test with no control group study design. Forty students were involved in this pilot study. A paper-based survey composed of a demographic section and a 5-point Likert (“1” is strongly disagree and “5” is strongly agree) section measured the students’ perceived learning outcome achievements after exposing them to clinical engineering major courses. A Wilcoxon signed-rank and Mann-Whitney U test statistics were conducted to test the two hypotheses of this study. Our analysis showed statistically significant results between the pre-survey mean and SD: 21.10 SD 3.54; and between the postsurvey mean and SD: 22.75 SD 3.68 (Z -2.12, p<0.033), indicating that overall, students’ perceived learning outcome achievements after exposing them to clinical engineering major courses had significantly improved by the end of the major. Also, statistically significant results were found between the post-survey mean and SD: 3.94 SD 0.61 learning outcome perceptions and between the students’ actual marks mean and SD: 4.53 SD 0.22 (-5.00, p<0.000), indicating the students had low confidence in their learning outcomes after completing their clinical engineering major.